Corruption Prevention Model Based on Mobile Banking - Prastyanti, Rina Arum; Yuliana, Margareta Evi; Sutrasno, Andi (Journal of Private and Commercial Law, 2019)
The advancement of internet technology and the rapid sales of smartphones in Indonesia become the third highest in the Pacific after China and India also have an impact on increasing mobile banking usage by 80% of bank customers in Indonesia. Kenya which is a poor and corrupt country in the world has made changes to the banking system, namely using an electronic platform called M-Pesa. M Pesa provides mobile-based payment and transfer services that can reduce corruption in the public sector. In Africa, Mobile phone signals and reach determine the success of corruption prevention using mobile banking. This study aims to obtain a corruption prevention model using mobile banking. This research is descriptive qualitative. The approach of this research is sociolegal study which is a study of law by using a legal science approach and social sciences. Data collection techniques using virtually research and library research The validity technique of the data used is data triangulation. Data analysis techniques in using technical qualitative analysis interactive models. The conclusion of this study is that the government must be able to take advantage of technological advances to combat corruption even though technology cannot replace a valid and evidence-based anti-corruption strategy, but technology can be used to help reduce corruption through mobile banking transactions.